PtI4-catalyzed oxidative and hydrogenative dearomative [3 + 2] cycloaddition of 1H-indole N-tethered o-alkynylbenzaldehydes. Issue 1 (23rd November 2022) - Shang, Dandan; Hu, Rui; Bao, Qing; Chen, Jichao; Yu, Lei; Chan, Philip Wai Hong; Rao, Weidong
Abstract : A method for the chemodivergent assembly of a diverse range of cyclohepta[ b ]indolines which relies on PtI4 -catalyzed oxidative and hydrogenative dearomative [3 + 2] cycloaddition of 1 H -indole N -tethered o -alkynylbenzaldehydes is described. Abstract : A synthetic method for the chemodivergent assembly of a diverse range of highly functionalized and architecturally challenging cyclohepta[ b ]indolines which relies on PtI4 -catalyzed oxidative and hydrogenative dearomative [3 + 2] cycloaddition of 1 H -indole N -tethered o -alkynylbenzaldehydes in a single operation is described. For the synthesis of a key structural feature that is found in a myriad of bioactive natural products and pharmaceutical compounds, the proposed cascade chemodivergent process delineates the first example of an in situ formed Pt-bound benzopyrylium intermediate that participates in [3 + 2] cycloaddition with the C(2)C(3) bond of an aromatic N-heterocycle as the 2π cycloaddition partner with exclusive exo -selectivity in a highly efficient manner. It also offers a unique instance of the resulting metallocarbene species generated in this manner undergoing either oxidation by phenylmethylsulfoxide or reduction by THF, with the solvent as both the hydride and alkyl reagent source. The chemodivergent protocol exhibits exceptional functional group tolerance and is amenable to the late-stage modification of a series of structurally complex bioactive natural products and drug molecules.